2007
DOI: 10.3200/jmbr.39.6.463-480
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Coordination of a Discrete Multiarticular Action as a Function of Skill Level

Abstract: The authors investigated coordination modes that emerged as a function of the interaction between skill level and task constraints in a multiarticular kicking action. Five skilled, 5 intermediate, and 5 novice participants attempted to satisfy specific height and accuracy constraints in kicking a ball over a barrier. Skilled and intermediate groups demonstrated a functional coordination mode involving less joint involvement at the proximal joints and greater joint involvement at distal joints, mimicking a chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 22 publications
6
33
1
Order By: Relevance
“…As well as improvement in physical performance, the results obtained in this study confirm the possibility that moderate intensity exercise also improve mental performance (Paas & Adam, 1991).The results also suggest that hand-eye coordination is sensitive to the short-term effects of exercise, mediated by several factors (Tomporowski & Ellis, 1986), such as physical fitness of subjects, intensity and duration of the exercise intervention, skills (Chow, Davids, Button & Koh, 2008) and the coordination tests selected.…”
Section: Discussionsupporting
confidence: 80%
“…As well as improvement in physical performance, the results obtained in this study confirm the possibility that moderate intensity exercise also improve mental performance (Paas & Adam, 1991).The results also suggest that hand-eye coordination is sensitive to the short-term effects of exercise, mediated by several factors (Tomporowski & Ellis, 1986), such as physical fitness of subjects, intensity and duration of the exercise intervention, skills (Chow, Davids, Button & Koh, 2008) and the coordination tests selected.…”
Section: Discussionsupporting
confidence: 80%
“…The results have indicated an improvement in visual skills as the participant's age increases. This could be attributed to the type of training that is being received and to the number of years that the player has been playing in his position because having accumulated visual skills his performance will be enhanced (Chow, Davids, Button & Koh, 2008). The results have also shown that different positions do not necessarily have different levels of visual skills.…”
Section: Discussionmentioning
confidence: 96%
“…Within this framework, there is no ideal motor coordination solution to be repeated, but rather functional patterns of coordination that emerge from the interaction of constraints (task, environmental and organismic) [1,18,22,23] leading to intraindividual and inter-individual movement variability. In previous research, the functional role of movement variability has typically been explored in performance of ball skills (in soccer [24]; in basketball [25,26]; in volleyball [27]; in handball [28,29]). Here we extend understanding by exemplifying how intra-individual and inter-individual movement variability could play a functional role in individual physical activities, such as a cyclical movement task (breaststroke swimming) in an aquatic environment and a continuous discrete task (ice climbing) in the wilderness.…”
Section: Introductionmentioning
confidence: 99%